Influence of the carrier type and surfactants on the trifuzole emission from veterinary intrauterine suppositorie - Bushuieva, I. V.; Klyosov, K. G.; Parchenk, V. V.; Gudzenko, O. P.; Gutyj, B. V.; Polova, Z. M.; Olkhovska, A. B.; Mykhailiuk, Ye. O.; Kurinnyi, A. V.; Gladysheva, S. A.; Odyntsova, V. M.; Бушуєва, Інна Володимирівна; et al. (My University, 2020)
The purpose of this work is to study the effect of excipients which are used in the technology of manufacturing veterinary suppositories (carrier bases and surface-active substances) on the emission of trifuzole, as the main biopharmaceutical characteristic of intrauterine veterinary dosage forms. An urgent problem of low reproductive ability are obstetric and gynecological diseases. The endometrial complex dominates in the frequency of manifestations of these diseases: placenta retention, metritis, endometritis and pyometra. These pathologies lead to a decrease in milk productivity and reproductive ability of animals. Antibacterial drugs are used for treatment, since their development is associated with damage to uterine tissues and the impact of microorganisms on it. However, this creates a certain problem with the quality of products in connection with the transfer of antibiotic substances into milk. Endometritis is more commonly reported among complex endometrial diseases. This disease is considered as a limited infection of the endometrium in the absence of systematic signs of the disease, but in the presence of purulent discharge (clinical endometritis) or the presence of leukocytes in the secretion of the uterus or cervix. Recently, endometritis of cattle is observed in almost 95% of farms in the world. This factor damages agriculture in countries up to $ 170 million per year. In this regard, the creation of new promising dosage forms for the treatment of this pathology (excluding the use of antibiotics) is extremely important. The composition and technology of the suppositories we offer requires a scientifically sound approach. In the work, methods of mathematical planning were applied, which made it possible to optimize research work, strictly individualize the selection of factors such as: properties, stability, bioavailability and pharmacotherapeutic effectiveness, which depend on the type of base, the nature of excipients, and the technology used. It is planned ahead to manufacture and sale the medicines on the internal and external pharmaceutical markets.
Keywords: endometritis; trifuzol; suppositories; carrier; surfactants